Estudio de factibilidad de la creación de una empresa productora y comercializadora de bolsos elaborados en telas, decorados a mano en el municipio de Zarzal, Valle del Cauca (2012)
The idea of ​​the project to create a production and marketing of hand-made cloth bags, arises in response to the business vision that is being acquired in the training process in the university where the desire to create opportunities that can be identified in the market that surrounds reasons have been made of relevant research of the project.